Preparing Faculty Using an Assessment for How Clinical Laboratory Students Learn. - Stewart, MaryAnne; Chojnacki, Roinette (Internet Journal of Allied Health Sciences & Practice, 2023)
Purpose: Students interpret and learn information in different ways. Whether students develop deep or surface learning depends in large part on the transmission of information from their educator, which activates their domains of learning. Knowing students' learning styles as either visual, auditory, psychomotor, or mixed, professors can develop teaching resources that benefit the learning diversity of their students by using different instructional delivery methods. This study examines survey results for how students learn best to enhance the student experience within the Clinical Laboratory Science (CLS) program at a university in Detroit, MI, USA. Method: To determine the resources needed to enhance learning for students and to prepare faculty, the cognitive learning styles of students within the last four cohorts of the CLS program were examined. To obtain this data, CLS students, from the 2018-2021 cohorts, participated in an online survey to discuss which cognitive learning styles they identified with based on the survey questions. Results: The majority of students did not just identify with one learning style. However, when presented with two or more learning styles, their retention of the material and experience was enhanced. Conclusion: Creating teaching resources for educators that revolve around multiple learning styles is necessary. Once established, the use of these resources can help enhance learning retention and thus encourage faculty members to thrive within the Clinical Laboratory Science program.